Exploring Challenges in Learning English: A Qualitative Case Study of Teacher Education Students in Indonesia - Restuti Nursafitri; Ita Sarmita Samad; Sri Rosmiana; Mustakim (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study explores the English learning difficulties faced by elementary school teacher education students in the Intensive English Program at Muhammadiyah University of Enrekang. Using a qualitative research design, data were collected through semi-structured interviews and document analysis involving 25 students from the 2020–2021 academic year. The study specifically examines the challenges these students encounter with grammar comprehension, vocabulary retention, and pronunciation fluency. Key findings reveal that these difficulties are exacerbated by psychological barriers such as anxiety, traditional teaching methods, and limited exposure to English outside the classroom. The research underscores the need for innovative, student-centered teaching strategies and contextualized learning methods to address these challenges. Practical solutions proposed include using interactive and communicative approaches, providing regular and constructive feedback, and fostering a supportive learning environment. These recommendations aim to improve English learning outcomes, contributing to the broader discourse on English as a Foreign Language (EFL) education. This study’s novel contribution lies in its specific focus on the unique learning difficulties encountered by students in the Indonesian context, offering actionable strategies for overcoming these barriers in similar settings.